Types and role of cytological molecular analysis in thyroid carcinomas - Nasser, Mohammad E.; Abdulrazaq, Aseel H.; Alrofydi, Abdullah M.; Hmdoon, Jumana M.; Alghamdi, Mohammed S.; Alsahli, Abdulaziz A.; Al Abdulwahhab, Mohammed A.; Alamri, Mesfer A.; Almotairi, Nawaf M.; Altamimi, Noora B.; Alghefari, Firas O. (International Journal Of Community Medicine And Public Health, 2021)
Estimates show that thyroid nodules are commonly reported among populations residing in iodine-sufficient countries, with estimated prevalence rates of 1%, and 4% of palpable nodules among men and women in these countries, respectively. Furthermore, early diagnosis can effectively direct clinicians to the right management modality, especially in cases with malignant lesions. In this literature review, we have discussed the types and roles of cytological molecular analysis in thyroid carcinomas. Our findings indicate the molecular analysis can significantly add to the diagnostic accuracy of cytological analysis and can greatly add to the efficacy of differentiating benign from malignant lesions. We have discussed the roles of different genetic mutations that were reported among the various studies in the literature, including BRAF, RAS, PAX8/PPARγ, and RET mutations. BRAF mutations are the most validated mutations among the current studies in the literature, which has been reported to greatly increase the positive predictive values in detecting thyroid carcinomas. Some genetic mutations can be used to diagnose difficult to differentiate malignancies by fine needle aspiration (FNA) analysis. For instance, RAS mutations were reported to accurately diagnose follicular variants of papillary thyroid carcinomas that are difficult to detect using routine FNA analysis.